Topical antihistamines, mast cell stabilizers, and dual-action agents in ocular allergy: current trends. Issue 5 (October 2018) - Ben-Eli, Hadas; Solomon, Abraham
Abstract : Purpose of review: To address the current trends of therapeutic mechanisms for treatment of allergic conjunctivitis (AC), based on topical antihistamines and mast cell stabilizers (MCS). Recent findings: The antihistamine drug alcaftadine has H4 receptor inverse agonism, anti-inflammatory and MCS activities. The antihistamines levocabastine and azelastine are more effective than placebo in treatment of AC symptoms in randomized controlled trials (RCTs). The topical dual-action antihistamines/MCS olopatadine, azelastine, ketotifen, and epinastine are commonly used in Europe and in the United States for mild subtypes of AC. For the main symptoms of AC, ocular itch and conjunctival hyperemia, epinastine 0.05% was superior to placebo, but equal or more effective than olopatadine 0.1%, while the later was more effective than ketotifen. High concentration olopatadine 0.77% had longer duration of action, better efficacy on ocular itch, and a similar safety profile to low-concentration olopatadine 0.2%. The new formulas of topical dual-action agents present longer duration of action, leading to a decreased frequency of use. Summary: The topical dual-action agents are the most effective agents treating signs and symptoms of mild forms of AC. There is superiority to the high-concentration olopatadine drug over other agents on ocular itch, with prolonged effect when used once-daily.